A practical guide to the assessment and management of acne vulgaris. Issue 2 (February 2023) - Ravenscroft, Jane; Wood, Damian; Layton, Alison
Abstract: Acne vulgaris (syn: acne) is very common and paediatricians are in an ideal position to assess a young person and start first line treatment. This article provides a practical guide to assessing a young person with acne, giving accurate information about the condition, and starting them on a treatment journey. The association between acne and mental health is considered and advice offered regarding which treatments to prescribe, for how long, when to review, and when to refer on to dermatology. Indications for topical treatments, antibiotics, hormonal treatments and oral isotretinoin are discussed.